Production Planning Towards Improving the Productivity Performance in Manufacturing Organization Using Arena Simulation - Rao, Andrian Raj; Ahmad, Ahmad Nur Aizat; Ahmad, Md Fauzi (Research in Management of Technology and Business, 2023)
The objective of this project is to develop a model, simulate and analyse a manufacturing system using ARENA The scope of the study is focused on automotive manufacturer, especially on the automotive parts stamping line. The goal is to provide the best methods to improve the efficiency of workstation processes and to ensure limitations and problems to achieve production targets. Procedure including data collection, model building, simulation, verification, and validation and performance analysis. To improve the understanding of ARENA, a case study was conducted out to make a simple simulation model. Then the model is simulated using the real one stamp production data collected including daily production index, process specifications, parameters, production schedule and machine breakdown. Output from simulations are generated in the form of reports. The report is organized by section which is summed across all replications. The results show that the error percentage of The ARENA model is less than 5% as targeted. This model will be used as a result support system for process improvement investigations by implementing several decisions such as balancing lines and simplifying operations. "What if" analysis is used check the submitted results. Findings confirm the qualitative the behavior of the manufacturing system in response to different decision options.